Characterizing the protonation states of the catalytic residues in apo and substrate-bound human T-cell leukemia virus type 1 protease. (June 2015) - Ma, Shuhua; Vogt, Kimberly A.; Petrillo, Natalie; Ruhoff, Alyce J.
Graphical abstract: Highlights: Protonation states of the catalytic residues in HTLV-1 protease were investigated. In apo HTLV-1 protease, the two catalytic residues are both unprotonated. In HTLV-1 protease–substrate complex, Asp32 is protonated, Asp32′ is unprotonated. Substrate binding favors a protonated Asp32 over protonated Asp32′ by 2.8 kcal/mol. The HTLV-1 protease–substrate complex structure was analyzed in detail. Abstract: Human T-cell leukemia virus type 1 (HTLV-1) protease is an attractive target when developing inhibitors to treat HTLV-1 associated diseases. To study the catalytic mechanism and design novel HTLV-1 protease inhibitors, the protonation states of the two catalytic aspartic acid residues must be determined. Free energy simulations have been conducted to study the proton transfer reaction between the catalytic residues of HTLV-1 protease using a combined quantum mechanical and molecular mechanical (QM/MM) molecular dynamics simulation. The free energy profiles for the reaction in the apo-enzyme and in an enzyme – substrate complex have been obtained. In the apo-enzyme, the two catalytic residues are chemically equivalent and are expected to be both unprotonated. Upon substrate binding, the catalytic residues of HTLV-1 protease evolve to a singly protonated state, in which the OD1 of Asp32 is protonated and forms a hydrogen bond with the OD1 of Asp32′, which is unprotonated. The HTLV-1 protease–substrate complex structure obtained from this simulation can serve as the Michaelis complex structure for further mechanistic studies of HTLV-1 protease while providing a receptor structure with the correct protonation states for the active site residues toward the design of novel HTLV-1 protease inhibitors through virtual screening.